HuR Plays a Positive Role to Strengthen the Signaling Pathways of CD4+ T Cell Activation and Th17 Cell Differentiation - Shiguang Yu; Morgan Tripod; Ulus Atasoy; Jing Chen (Journal of Immunology Research)
After antigen and/or different cytokine stimulation, CD4+ T cells activated and differentiated into distinct T helper (Th) cells via differential T cell signaling pathways. Transcriptional regulation of the activation and differentiation of naïve CD4+ T cells into distinct lineage Th cells such as Th17 cells has been fully studied. However, the role of RNA-binding protein HuR in the signaling pathways of their activation and differentiation has not been well characterized. Here, we used HuR conditional knockout (HuR KO) CD4+ T cells to study mechanisms underlying HuR regulation of T cell activation and differentiation through distinct signaling pathways. Our work showed that, mechanistically, HuR positively promoted CD3g expression by binding its mRNA and enhanced the expression of downstream adaptor Zap70 and Malt1 in activated CD4+ T cells. Compared to WT Th0 cells, HuR KO Th0 cells with reduced Bcl-2 expression are much more susceptible to apoptosis than WT Th0 cells. We also found that HuR stabilized IL-6Rα mRNA and promoted IL-6Rα protein expression, thereby upregulating its downstream phosphorylation of Jak1 and Stat3 and increased level of phosphorylation of IκBα to facilitate Th17 cell differentiation. However, knockout of HuR increased IL-22 production in Th17 cells, which was due to HuR deficiency in reducing IL-22 transcription repressor c-Maf expression. These results highlight the importance of HuR in TCR signaling and IL-6/IL-6R axis driving naïve CD4+ T cell activation and differentiation into Th17 cells.